2018
DOI: 10.21608/resoncol.2018.3478.1056
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Study of Burnout among a Group of Egyptian Oncologists at Ain Shams University

Abstract: Background: Oncologists are at risk of developing burn out syndrome due to many stressors they may face. Aim: To determine the level of burnout in a cohort of clinical oncologists working in an Egyptian university hospital. Methods: Fifty-two clinical oncologists were invited to participate in the study. Burnout was assessed using the Arabic version of Maslach Burnout Inventory Human Services Survey (MBI-HSS). Results: The response rate was 90% (47/52). The majority (70%) of responders were young oncologists a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…These results may reflect gender differences in DP. Although most oncologist studies included in the meta-analysis had relatively equal representation of men and women (e.g., Eelen et al, 2014; Ghali et al, 2018), there was a higher proportion of women among the oncology nurse studies (e.g., Neumann et al, 2018; Ramirez-Baena et al, 2019). Gender differences regarding DP were also exemplified in previous studies, with men having a higher risk of DP compared with women (Purvanova & Muros, 2010; Putnik & Houkes, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These results may reflect gender differences in DP. Although most oncologist studies included in the meta-analysis had relatively equal representation of men and women (e.g., Eelen et al, 2014; Ghali et al, 2018), there was a higher proportion of women among the oncology nurse studies (e.g., Neumann et al, 2018; Ramirez-Baena et al, 2019). Gender differences regarding DP were also exemplified in previous studies, with men having a higher risk of DP compared with women (Purvanova & Muros, 2010; Putnik & Houkes, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Argentina, a LMIC, during the third wave of COVID-19 pandemic found the burnout among the medical oncologists to vary between 14.9 and 47.9 based on different burnout scales they used [31]. In Egypt, before the COVID-19 pandemic, a single institution study showed oncologists were suffering from burnout: 72% had emotional exhaustion, 49% depersonalization, and 38% personal accomplishment [32]. After the beginning of the COVID-19 pandemic, a multi-center study reported 32% of the Egyptian oncologists having burnout syndrome [33].…”
Section: Discussionmentioning
confidence: 99%
“…Burnout and the inability to have a healthy worklife balance are the most serious challenges in our working environment. According to a recently published survey study at the AS clinical oncology department, 72% of participants (52 clinical oncologists) had burnout on the emotional exhaustion (EE) scale, 49% on the depersonalization (DP) scale, and 38% on the personal accomplishment (PA) scale (Ghali et al 2019).…”
Section: Burnoutmentioning
confidence: 99%